Martin Fishbein's Multiattribute Analysis on Using The Pegadaian Digital Service PT Pegadaian Indonesian Pawnshop - Avrianto, Alam; Murwenie, Ira (Sainteks: Jurnal Sain dan Teknik, 2024)
The objective of this investigation is to assess the level of client trust and the attitude of PT. Pegadaian Indonesia toward the Pegadaian Digital Services (PDS) Application. The PDS Application is an internet-based pawn service application that was launched by PT. Pegadaian Indonesia in 2021. This study is a quantitative research study that aims to gather data from a specific group of clients of PT. Pegadaian Indonesia KCU Gegerkalong - Bandung. The data collection will be done using deliberate random sampling procedures. The analytical methodology utilized is the Martin Fishbein multi-attribute analysis model, implemented through the utilization of Ms Excel software version 13. The findings of this research will be advantageous in assessing the degree of perception and level of confidence that consumers of PT. Pegadaian Indonesia have in the utilization of the PDS Application. This application has been offered by PT. Pegadaian Indonesia to facilitate its online gold collateral and loan services.